Instrumento de avaliação da gestão para centros federais de educação tecnológica utilizando critérios de prêmios da qualidade - Espíndola, Celso da Silva (2007)
The Brazilian higher education is going through a moment of changes that consolidates an educational politics for the upper education. Among those reforms, is the National Evaluation System of Higher Education (SINAES), developed to evaluate the Brazilian higher education in 3 (three) evaluation instrument modalities, applied in different moments: evaluation of the higher institutions education; internal or auto evaluation, and external evaluation; evaluation of the graduation courses; and evaluation of the students performance. The present work develops and applies an instrument of internal evaluation of the management for the Federal Technological Education Centers (CEFETs), utilizing excellence criteria of quality prizes, focused in the higher courses in technology, with purpose of not just the fulfillment of the phases defined by the SINAES, but also the improvement of the academic quality and the institutional development. The instrument is based on the quality principles, associated to the use of statistical techniques, whose objective is to evaluate internally the management of CEFETs, in the dimensions of managerial processes and organizational results. To verify its applicability, the instrument was applied in the Federal Technological Education Center of Goiás (CEFETGO) - Unit of Goiânia. Considering its first experience of promoting the evaluation of the institutional management, the result presents adequate approaches for the requirements of almost all of the items, being several of them proactive disseminated by the main areas, processes, products and/or involved parts; continued use in barely all the practices, with active controls; there are some innovations and many refinements resulting of the training; the practices of management are coherent with the organizational strategies, there are some gaps of the inter-relationship among the management practices; there are many gaps of cooperation between areas and/or involved parts, affecting regularly the integration; the majority of the results presents favorable tendency; the present level of maturity achieved.